Views of men with Parkinson's disease regarding physical activity health messaging. Issue 1 (January 2023) - da Silva, Karis; Baxter, G David; Calder, Allyson
Abstract: Background: Many men with Parkinson's Disease (PD) do not meet the recommended levels of physical activity (PA) for health benefits. Tailored, meaningful, and culturally sensitive PA health messages may be a catalyst to shape men's motivations toward participation. Objective: We explored the views of New Zealand (NZ) men with PD about existing PA health messages, and how these could be adapted to be more effective. Methods: This qualitative study recruited six community dwelling, regularly physically active, NZ European men with PD (aged 54–69 years, 2–18 years post-diagnosis) from a community exercise class in Canterbury, NZ. Participants engaged in semi-structured interviews which were audio-recorded, transcribed verbatim, and analyzed inductively for themes. Results: Participants expressed that effective PA health messages should reflect men's motivations for PA which included physical and mental well-being and social connection. Inclusive, positive, and relatable language and imagery were considered crucial PA message communication strategies. Participants viewed health professionals' PA advice as superficial and unhelpful; however, celebrities with PD were considered inspirational messengers. Messages endorsed by trustworthy sources, such as the Parkinson's Society, were perceived to enhance the credibility. Conclusions: Effective PA messages should be gain framed and tailored to the target audience. We recommend health professionals provide comprehensive PA advice or consider onward referral. Future research which uses a co-design participatory methodology to collaborate with men with PD from culturally diverse backgrounds and represent all stages of PA behaviour change is recommended to provide comprehensive insights for meaningful, effective, and culturally sensitive PA health messaging.